Religion and Religiousity in Public Mental Health Policies: The challenges to completeness care (Research, Society and Development, 2025)
In Brazil, the religious dimension has always been a striking characteristic of its population. According to data from the Brazilian Institute of Geography and Statistics (IBGE), in 2022, 76% of Brazilians said they follow some religion, exceeding the global average of 67%. The concept of health, expanded by the WHO in the 1940s, began to include physical, mental and social well-being. This study aims to analyze how religious practices influence mental health care within the context of the SUS. A bibliographic review was carried out in databases such as Scielo, LILACS and VHL, using the descriptors "Mental Health", "Religion and Medicine" and "Integrality in Health". Articles from the last ten years were included and those with methodologies with low scientific rigor were exclude. The study identified a great diversity in religious practices in the treatment of mental imbalances in Brazil, such as prayer, spiritual counseling and religious rituals. However, some religious groups resist the integration of conventional mental health approaches, prioritizing spiritual methods. Lack of effective communication between healthcare professionals and religious leaders contributes to barriers to collaboration. To improve mental health care in the SUS, it is necessary to train mental health professionals, raise awareness in the community through public education and create spaces for interreligious and interdisciplinary dialogue. Clear ethical guidelines are also essential to respectfully and effectively integrate religious practices into mental health care, balancing Brazil's cultural and religious diversity.